1990
DOI: 10.1111/j.1423-0410.1990.tb02089.x
|View full text |Cite
|
Sign up to set email alerts
|

Histological and Immunohistochemical Studies on the Preparation of Leukocyte‐Poor Red Cell Concentrates by Filtration: The Filtration Process on Cellulose Acetate Fibers

Abstract: A histological and immunohistochemical investigation of slices from the Cellselect leukocyte filter showed that the capture of lymphocytes within these filters depended on trapping of the cells in the cellulose acetate fiber network more than on adherence. Probably, additional mechanisms played a role in granulocyte removal. Microaggregates of granulocytes and platelets were found at the top of the Cellselect leukocyte filter. Therefore, it is likely that granulocyte and platelet removal, at least in part, is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Cotton wool fibers were first used as the filter material to remove leucocytes from blood [6]. Subsequently, different synthetic material fibers were developed for the leucocyte filtration technique, which includes cellulose acetate [7], polyethylene terephthalate (PET) [5], polyurethane [8], polybutylene terephthalate [9,10], polypropylene (PP) [11], polyethylene vinyl alcohol (EVAL) [12], etc. In addition, recent studies of leucocyte depletion techniques revealed that many physical and chemical methods were used for modifying material surface characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Cotton wool fibers were first used as the filter material to remove leucocytes from blood [6]. Subsequently, different synthetic material fibers were developed for the leucocyte filtration technique, which includes cellulose acetate [7], polyethylene terephthalate (PET) [5], polyurethane [8], polybutylene terephthalate [9,10], polypropylene (PP) [11], polyethylene vinyl alcohol (EVAL) [12], etc. In addition, recent studies of leucocyte depletion techniques revealed that many physical and chemical methods were used for modifying material surface characteristics.…”
Section: Introductionmentioning
confidence: 99%